Projeto e construção de lajes pré-moldades de concreto armado - Santine, Carlos Roberto (Universidade Federal de São Carlos, 2005)
This work presents the main recommendations for the design of precast slabs strips, comprising precast lattices and infill elements, strengthened by cast-in-situ concrete overlay. Based on Brazilian codes of practice for precast slabs, this work describes characteristics of materials, discusses the main design requirements and analytical models as well as verifications at the serviceability limit state. This work emphasises a methodology that considers the nonlinear behaviour the reinforced concrete, describing the proposed formulations to determine the moment of inertia based on a cracked section, using software that allows for the incremental loading technique. Using this method a better approximation for the real performance of the reinforced concrete structure is obtained. Finally, this work proposes a new type for precast slabs strips, without the lattice truss reinforcement, which may become an innovative technology for the precast sector in Brazil.
Keywords: Concreto armado; Lajes pré-moldadas; Lajes treliças; Lajes nervuradas; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL